The CO-dark molecular gas mass in 30 Doradus - Chevance, Mélanie; Madden, Suzanne C.; Fischer, Christian; Vacca, William D.; Lebouteiller, Vianney; Fadda, Dario; Galliano, Frédéric; Indebetouw, Remy; Kruijssen, Diederik; Lee, Min-Young; Poglitsch, Albrecht; Polles, Fiorella L.; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Determining the efficiency with which gas is converted into stars in galaxies requires an accurate determination of the total reservoir of molecular